The investigation of peripheral blood cellular immune responses during infection with Mycobacterium Tuberculosis - Veenstra, Hannelore F. U. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2007.